Corrosion behaviour of Ti-6A1-4V simulated body fluid for implant [compact disc] - 214550 Jamillah Amer Nordin (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2006